2015
DOI: 10.1021/acs.jproteome.5b00654
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Different Sample Preparation Protocols Reveals Lysis Buffer-Specific Extraction Biases in Gram-Negative Bacteria and Human Cells

Abstract: We evaluated different in-solution and FASP-based sample preparation strategies for absolute protein quantification. Label-free quantification (LFQ) was employed to compare different sample preparation strategies in the bacterium Pseudomonas aeruginosa and human embryonic kidney cells (HEK), and organismal-specific differences in general performance and enrichment of specific protein classes were noted. The original FASP protocol globally enriched for most proteins in the bacterial sample, whereas the sodium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 67 publications
2
94
1
1
Order By: Relevance
“…Here we used our MS1-based LFQ workflow as a reference method, as this had previously been demonstrated to reliably detect protein concentration differences across complex mixtures 22,23 In this investigation a second set of 2-proteome samples was prepared to produce two B. henselae proteome reference ratios; 1.5:1 and 2:1 and a 1:1 human proteome background (2-Proteome-Precision samples; see Experimental Section for details). All samples were acquired in triplicates using our LFQ and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 TMT-6-plex.…”
Section: Comparing Tmt To Ms1-based Label Free Quantificationmentioning
confidence: 99%
“…Here we used our MS1-based LFQ workflow as a reference method, as this had previously been demonstrated to reliably detect protein concentration differences across complex mixtures 22,23 In this investigation a second set of 2-proteome samples was prepared to produce two B. henselae proteome reference ratios; 1.5:1 and 2:1 and a 1:1 human proteome background (2-Proteome-Precision samples; see Experimental Section for details). All samples were acquired in triplicates using our LFQ and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 TMT-6-plex.…”
Section: Comparing Tmt To Ms1-based Label Free Quantificationmentioning
confidence: 99%
“…Glatter et al compared the global proteome extraction differences between in-solution and FASP-based sample preparation strategies. 22 Both bacteria and human cells were investigated in the study where the inconsistency of extraction efficiency was observed between two sample types. Although the results provide more insights into the organism specific quantitative bias from different sample preparation methods, the LC-MS method was not optimized for maximizing the peptide identification (ID) and quantification, rendering less than half of the proteins that were identified from the entire proteome.…”
Section: Introductionmentioning
confidence: 99%
“…There is no universal protein extraction method which enables the successful extraction of the total protein from all types of human tissues . The RHE method and c T/AHE method were originally selected to study the efficiency of these methods to extract proteins from placental cotyledons tissues.…”
Section: Resultsmentioning
confidence: 99%
“…C, red box, blue box, green box, and yellow box). This might be due to selected protein lysis buffer which is coupled with selected protein precipitation methods required to extract certain proteins .…”
Section: Resultsmentioning
confidence: 99%